Innovation Marketing in Electronic Ticketing System and Strategic Relationship in Public Transport - Azamat Berdiyorov, Temur Berdiyorov, Shaxnoza Ergashxodjaeva, Nilufar Berdiyorova (International Journal of Advanced Science and Technology, 2020)
Interest in the services sector has grown and has assumed an important role in emerging economies. This article presents a study of multiple cases that pursued to analyze the marketing of innovation in services, on the perspective of the implementation of electronic ticketing among the associated companies of public transport. It was observed that the technology used in the electronic ticketing system is considered the greatest technological innovation for the associated companies in recent years and that it opens possibilities of revolutionizing the control and marketing models of public transportation. Finally, with regard to innovation in services, it should be noted that improvements related to companies and their methods in the integration of activities seem to be a promising way to meet the demands of an increasingly demanding and selective consumer market; as well as to obtain relevant gains in a sector in full decline.